Home Away From Home: Bioengineering Advancements to Mimic the Developmental and Adult Stem Cell Niche - Barhouse, Patrick S.; Andrade, Melisa J.; Smith, Quinton (Frontiers in Chemical Engineering, 2022)
The inherent self-organizing capacity of pluripotent and adult stem cell populations has advanced our fundamental understanding of processes that drive human development, homeostasis, regeneration, and disease progression. Translating these principles into in vitro model systems has been achieved with the advent of organoid technology, driving innovation to harness patient-specific, cell-laden regenerative constructs that can be engineered to augment or replace diseased tissue. While developmental organization and regenerative adult stem cell niches are tightly regulated in vivo, in vitro analogs lack defined architecture and presentation of physicochemical cues, leading to the unhindered arrangement of mini-tissues that lack complete physiological mimicry. This review aims to highlight the recent integrative engineering approaches that elicit spatio-temporal control of the extracellular niche to direct the structural and functional maturation of pluripotent and adult stem cell derivatives. While the advances presented here leverage multi-pronged strategies ranging from synthetic biology to microfabrication technologies, the methods converge on recreating the biochemical and biophysical milieu of the native tissue to be modeled or regenerated.